A SISTEM INFORMASI INVENTARIS BERBASIS ANDROID MENGGUNAKAN METODE CLIENT SERVER - Aditian, Fraz; Hidayah, Agung Kharisma (UNIVED Press, 2021)
The development of technology and information has many positive impacts in various areas of life. Inventory of goods is the recording of data related to goods or assets in the organization. Generally, activities in goods inventory are recording goods procurement, placement, transfer and maintenance. The inventory process of goods carried out by the Permu village of Kepahiang Regency still uses manual recording in an inventory book. From the problems above, an Android-based goods inventory information system is needed using a client server system. The information system that will be created uses the Java programming language with MySQL as the database. So the formulation of the problem is that there is no Android-based inventory information system using the client server method. The aim of this research is to be able to provide information on inventory of goods based on android using the client server method in villages permu Kepahiang Regency. It is hoped that this application is always up to date so that this application follows developments in geographical information technology based on Android Flutter.